Randomised clinical trial: colestyramine vs. hydroxypropyl cellulose in patients with functional chronic watery diarrhoea. Issue 11 (10th April 2015) - Fernández‐Bañares, F.; Rosinach, M.; Piqueras, M.; Ruiz‐Cerulla, A.; Modolell, I.; Zabana, Y.; Guardiola, J.; Esteve, M.
Summary Background Idiopathic bile acid malabsorption (BAM) has been suggested as a cause of chronic watery diarrhoea, with a response to colestyramine in 70% of patients. However, the efficacy of this drug has never been investigated in placebo‐controlled trials. Aim To evaluate the efficacy of colestyramine as compared with hydroxypropyl cellulose in the treatment of functional chronic watery diarrhoea. Methods Patients with chronic watery diarrhoea were randomly assigned to groups given colestyramine sachets 4 g twice daily (n = 13) or identical hydroxypropyl cellulose sachets (n = 13) for 8 weeks. The primary end‐point was clinical remission defined as a mean of 3 or fewer stools per day during the week before the visit, with less than 1 watery stool per day. A secondary end‐point was the reduction in daily watery stool number. SeHCAT test was performed in all patients, but an abnormal test was not a prerequisite to be included. Results All included patients had a SeHCAT 7‐day retention ≤20%. There were no statistical differences in the percentage of patients in clinical remission at week 8 between colestyramine and hydroxypropyl cellulose with either intention‐to‐treat (53.8% vs. 38.4%; P = 0.43) or per‐protocol (63.6% vs. 38.4%; P = 0.22) analyses. However, the mean per cent decrease in watery stool number was significantly higher with colestyramine than with hydroxypropyl cellulose (−92.4 ± 3.5% vs. −75.8 ± 7.1%; P = 0.048). The rate of adverse events related to study drugs did not differ between groups. Conclusions Colestyramine (4 g twice daily) is effective and safe for short‐term treatment of patients with chronic watery diarrhoea presumably secondary to BAM. Clinical Trials Register number EudraCT 2009‐011149‐14.